Review of the South American-Antarctic Triplefin Fish Genus Helcogrammoides (Perciformes: Tripterygiidae) - Williams, Jeffrey T. (2001)
The genus Helcogrammoides comprises three species of small, cryptic shorefishes, H. antarcticus, H. chilensis, and H. cunninghami. All three species inhabit shallow water along exposed rocky coasts. Specimens reported herein extend the known distributions of H. chilensis and H. cunninghami to the vicinity of Lima, Peru, approximately 1600 km north of their previously reported northernmost records in Chile. Helcogrammoides chilensis and H. cunninghami occur sympatrically over most of their ranges in Peru and Chile and are frequently taken together in the same field collections. Lectotypes are designated for H. chilensis and H. cunninghami. Diagnoses and an identification key are provided for the species.